Potential of Pummelo Citrus Fruit Extract (Citrus maxima), the Magetan Typical Plant as an Anti-Breast Cancer Agent - Vevi Maritha; Dudy Eko Handoko (Alliance oh Health Activists (AloHA), 2020)
The pummelo orange may be potential as an anti-breast cancer agent because it contains lycopene compounds. Lycopene works by suppressing cell proliferation or multiplication. In breast cancer patients, cell multiplication occurs very rapidly. Lycopene is also able to slow down or even prevent the oxidation process of other molecules and eliminate free radicals in the body that can cause cell damage. Free radicals can bind to DNA, protein, and lipid which will damage their physiological functions, which in turn can lead to the development of breast cancer. Lycopene is a very effective free radical eliminator. Through these two mechanisms, suppressing cell multiplication and eliminating free radicals, lycopene might be used as a breast cancer therapy. The cytotoxic activity test of pummelo citrus fruit extract was carried out using the MTT method on MCF-7 cells. The pummelo citrus fruit was extracted by maceration method using 96% ethanol as a solvent. Breast cancer cell cultures (MCF-7 cells) were transferred as many as 1x104 cells/well in culture media which consisting of FBS, penicillin-streptomycin, amphotericin-B and RPMI 1640 into 96-well plates and incubated in a 5% CO2 incubator overnight. Furthermore, the test sample was given with a series of levels and made replications three times (triple), then incubated again overnight. On the third day, we added MTT reagent, and after 4 hours the formazan crystals were formed in the living cells. Furthermore, a SDS stopper was added to stop the MTT reaction. Then, the absorbance reading was carried out using an ELISA reader at a wavelength of 595 nm and continued to determine the value of IC50. The results showed that the IC50 value of pummelo orange extract was 234 µg/µL. It showed that pummelo orange extract had potential as an anti-breast cancer agent. This study could contribute to the development of breast cancer drugs. Pummelo fruit extract which is selective against cancer cells can be the therapy of choice in the treatment of breast cancer patients whose prevalence is high in Indonesia. Keywords: breast cancer, cytotoxic activity, pummelo, lycopene